Analysis on the epidemiological and drug resistance characteristics of osteoarticular tuberculosis in South-central China - Fang, Tanwei; Yang, Shuliu; Liu, Binbin; Li, Wenbin; Sun, Qing; Liu, Haican; Yu, Yanyan; Xiang, Yu; Li, Machao; Guo, Yi; Li, Jixiang; Zhao, Xiuqin; et al. (Frontiers in Public Health, 2024)
Objective: Osteoarticular tuberculosis (OATB) is one of the most common forms of extrapulmonary tuberculosis; however, limited epidemiological data are available on this public health concern worldwide, especially in developing countries. This study aimed to analyze the clinical epidemiology and drug resistance characteristics of OATB cases in Hunan province which located in South-central China. Methods: We retrospectively enrolled OATB patients with Mycobacterium tuberculosis culture positive at Hunan Chest Hospital from January 2013 through March 31, 2022. The multiple demographic, clinical variables and drug susceptibility data of the patients were collected from the hospital's electronic patient record. Descriptive statistical methods, Chi-square test and logistic regression analysis were employed as statistical methods. Results: Of the 269 OATB cases, 197 (73.23%) were males, 206 (76.85%) were farmers; patients' ages ranged from 5 to 85 years, 57 (21.19%) aged at 20 29 years old and 52 (19.33%) aged at 60 69 years old. In terms of the disease, 177 (65.80%) had spinal TB with most occurrence in lumbar vertebra (26.02%, 70/269), multiple spinal sites (18.96%, 51/269) and thoracic vertebrae (15.24%, 41/269). Outside of the spine, OATB mainly occurred in the lower limb (13.38%, 36/269). In terms of drug resistance, 40 (14.87%) and 72 (26.77%) were resistant to rifampicin (RFP) and isoniazid (INH)respectively; 38 (14.13%) were multi-drug resistant (MDR), and a total of 78 (29.00%) isolates were drug resistant. OATB patients aged 40 49 years old (compared to those aged ≥70 years) and from the west of Hunan province, China (compared to those from the center of Hunan) were at risk for developing RR/MDR (ORs were 5.057 and 4.942, respectively; 95% CIs were 1. 009-25.342 and 1.458-16.750, respectively).In South-central China, OATB mainly affected males, farmers and those aged 20 29 and 60 69 years old. Spinal TB is prone to occur in the lumbar and multiple spinal sites. The resistance situation of OATB was serious, and people aged 40 49 years old and patients from the west of Hunan were risk factors of RR/MDR. All these findings will help to improve the prevention, diagnosis and treatment strategies of OATB.